TINJAUAN EKSTENSIFIKASI BARANG KENA CUKAI PADA TAS PLASTIK - Mohammad Zainul Abidin (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
The aims of this research was first, examining the possibility imposition of excise plastic bags under Law 39/2007 and second, observing of the Government efforts to protect the environment through the plastic bag excise. This research used method focused on the research literature to obtain the literature data or secondary data. The specification of this research used wasanalytical descriptive as it strives to provide descriptions and to analyze of the object by utilizing the economic theories and laws. Pursuant to the research result, the conclusion can be said that based on Article 2 paragraph (1) of Law 39/2007 on Amendment to Law Number 11 Year 1995 regarding Customs, plastic bags are eligible to be categorized as goods subject to excise because it has natures and characteristics of the goods subject to excise. Imposition of excise tax on plastic bags is based on an effort to protect the public safety and environmental through controlling its circulation. To reduce the negative impact of the use of plastic bags, Government might impose of excise duty plastic bag by proposes plastic bag as excisable goods in the Budget Law and disseminating information about excise of plastic bags to other parties/society.